Effect of high-speed strength training on physical performance in young soccer players of different ages - Rodriguez-Rosell, D.; Franco-Marquez, F.; Mora-Custodio, R.; Gonzalez-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2017)
The aim of the present study was to compare the effectiveness of low-load, low-volume weight training combined with plyometrics on strength, sprint, and jump performance in soccer players of different ages. Eighty-six soccer players from the same academy were categorized into 3 groups by age (under 13 years, U13, n = 30; under 15, U15, n = 28; and under 17, U17, n = 28) and then randomly assigned into 2 subgroups: a strength training group (STG) and a control group (CG). The strength training program was performed twice a week for 6 weeks and consisted of full squats (load: 45-60% 1 repetition maximum; volume: 3 set of 8-4 repetitions), jumps, and straight line sprint exercises. After training intervention, the STGs showed significant improvements in maximal strength (7.5-54.5%; p < 0.001), jump height (5.7-12.5%; p <0.01-0.001), and sprint time (-3.7 to -1.2%; p =0.05-0.001), whereas no significant gains were found for any variable in the CGs. Comparison between experimental groups resulted in a greater magnitude of change for U13 compared with U15 (effect sizes [ES]: 0.10-0.53) and U17 (ES: 0.14-1.41) soccer players in most variables, whereas U15 showed higher improvements in jump and strength parameters than U17 (ES: 0.25-0.90) soccer players. Thus, although our results indicates that a combined weight training and plyometrics program may be effective in eliciting gains in strength, jump, and sprint in soccer players of different ages, the training program used appears to be generally less effective as the age of the soccer players increased. Therefore, it appears that training characteristics (mainly volume, intensity, and type of exercise) should be modified in relation to maturity status and initial strength level.